The Impact of Leadership Style on Employee Performance at the Public Works Office of East Luwu Regency - Nurfaisah Nurfaisah; Muh Ramli; Samsuri Samsuri; Rafika Fausiah (Universitas Muhammadiyah Makassar, 2023)
Leadership, Transactional Leadership, and Motivation with the Performance of Public Works Department employees of East Luwu Regency on the performance of district public works employees. East Luwu. This research was conducted with the aim of: (1) analyzing the transformational leadership style on employee performance, (2) analyzing the effect of transactional leadership style on employee performance, (3) analyzing the effect of motivational style on employee performance, (4) analyzing which leadership style is has the most dominant influence on employee performance. The results of this study are waiting for a saturated sample where the total population of 49 people is used as the research sample, the survey was conducted from August to September. The results of this study show that: (1) transformational leadership style has a positive but not significant effect on employee performance (2) transactional leadership style has a negative but not significant effect on employee performance, (3) motivation has a positive but not significant effect on employee performance, ( 4) motivation is the dominant factor influencing leadership style, (5) the contribution of transformational leadership, transactional leadership, and motivation on employee performance is 19.9%.This means that a good leadership style is one of the determining factors for employee performance.